Promoting adolescent health: health literacy, self-efficacy and internet use - Ceylan, Dilara; Akan-Çelen, Feyza Nur; Özkan, Seçil; Aycan, Zehra (The Turkish Journal of Pediatrics, 2022)
Background. Adolescents are mostly considered as a healthy population; however, failure to acquire positive health behaviors during this period makes them vulnerable to poor health outcomes and long-term chronic disorders. Health literacy is one of the most influential parameters in promoting adolescent health. This study aimed to determine the level and promoters of health literacy in adolescents, emphasize the importance of internet use, and evaluate the relationship between self-efficacy and health literacy. Methods. A total of 756 adolescents aged 15 and 18 years attending two high schools in socioeconomically different districts in Ankara, Turkey were included in this cross-sectional study. A survey consisting of descriptive questions, a health literacy survey, and a general self-efficacy scale were used to collect data. p < 0.05 was considered statistically significant. Results. Among the adolescents who participated in the study, the level of health literacy was inadequatelimited in 56.1%, sufficient in 30.1%, and excellent in 13.8%. A statistically significant correlation was found between health literacy and general self-efficacy levels (r: .412, p < 0.001). There was also a statistically significant difference between the health literacy groups in terms of the education level of the adolescents` mothers, internet use frequency, and self-efficacy level. The multivariate logistic regression analysis revealed that the participants whose mothers had only received primary school education or no formal education, those that were not using the internet regularly, those that did not search health information on the internet, and those with poor self-efficacy levels were more likely to have an inadequate level of health literacy [odds ratio (OR)=2.6, 95% confidence interval (CI)=1.4-4.9; OR=5.5, 95% CI=1.2-25.1; OR=1.7, 95% CI=1.1-2.9; and OR=3.7, 95% CI=2.6- 5.2, respectively]. Conclusions. In this study, it was concluded that the adolescents` health literacy and general self-efficacy levels were related. Furthermore, the health literacy level of the adolescents was associated with internet use and maternal education status.
Keywords: adolescent; health literacy; internet use; self-efficacy